Interpersonal relationship, workload pressure, work environment, and job stress among hospitality internships - Revathy Sivaguru; Nor Aidah Tonmezi @ Tarmezi; Nor Akmalisa Azwani Hamadan; Muhammad Faris Mohd Saidi (2022)
Job stress is a type of stress that is induced by work situations that negatively impact an individual's performance and/or physical well-being. Internships are crucial in all businesses, but in the hospitality industry, the more experience a student can gain "serving" customers and guests, the better their chances of promotion. Interpersonal interactions, workload pressure, work environment, and job stress levels are investigated among hospitality internship students in this study. The goal of this study is to discover and examine the link between interpersonal relationships, workload pressure, and work environment and job stress among hospitality internship students. A total of 177 people took part in this study, which was performed using a Google form. This research focused on University Malaysia Kelantan hospitality internship students. The findings revealed that work environment, workload pressure, and interpersonal relationships all play a significant influence in causing workplace stress among hospitality internship students.